Injuries in equestrian vaulting: results of a prospective study - Zarghooni, K.; Hub, L.; Bredow, J.; Yagdiran, A.; Hackenberg, R. K.; Scheyerer, M.; Westermann, L.; Eysel, P.; Siewe, J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Equestrian vaulting is a sport, particularly popular among children and adolescents, in which gymnastic and dance routines are performed on horseback. Current data regarding injuries and thus, the risks of this sport, is meager and based only on retrospective studies. METHODS: In the current prospective study, 233 active members of a vaulting club were questioned monthly from November 2014 until October 2015. In addition to general information (training, competitions), the questionnaire collected the number of competitions, the competitive class, the discipline (single, team, Pas-de-Deux), and injuries (type, localization, treatment). RESULTS: There were 102 documented events resulting in 125 injuries, yielding an average 31.64 days of training lost. Each vaulter suffered an average 0.44 injuries per year. Frequency of injury was 2.15 injuries per 1000 training hours. Injuries occurred most often to the lower and upper extremities. Most common were bruises and muscle injuries. Injury risk increased with increasing age, number of falls from the horse, increasing competitive level, number of tournament entries and events (P=0.006), and previous injuries (P=0.010). CONCLUSIONS: Our study found that vaulting has a low risk of injury comparable to non-contact sports. The best focus for injury prevention strategies is on older vaulters at higher competitive levels performing more complex routines.